Mid- to Long-Term Clinical and Echocardiographic Effects of Post-procedural Permanent Pacemaker Implantation After Transcatheter Aortic Valve Replacement: A Systematic Review and Meta-Analysis - Xu, Shun; Zhang, Enrui; Qian, Zhiyong; Sun, Jinyu; Zou, Fengwei; Wang, Yao; Hou, Xiaofeng; Zou, Jiangang (Frontiers in Cardiovascular Medicine, 2022)
Aims: To date, the prognostic effects of permanent pacemaker implantation (PPI) after transcatheter aortic valve replacement (TAVR) remain controversial. The purpose of this meta‐analysis was to investigate the mid- (1 year) to long-term (> 1 year) clinical and echocardiographic effects of postprocedural PPI in patients after TAVR. Methods: PubMed, Embase, Web of Science, and Cochrane Library databases were systematically searched from the establishment of databases up to 1 December 2021. Studies comparing clinical and echocardiographic outcomes between patients with and without post-TAVR PPI of ≥ 1-year follow-up were collected for further meta-analysis. Results: A total of 39 studies comprising of 83082 patients were included in this meta-analysis. At mid-term follow-up (1 year), the pooled results demonstrated a higher risk of all-cause mortality in patients with post-procedural PPI than those without following TAVR (RR, 1.17; 95% CI, 1.10 to 1.24; P < 0.00001). No significant differences were observed in cardiovascular mortality (RR, 0.86; 95% CI, 0.71 to 1.03; P = 0.10) or heart failure rehospitalization (RR, 0.91; 95% CI, 0.58 to 1.44; P = 0.69) at 1-year follow-up. At long-term follow-up (>1 year), post-TAVR PPI had negative effects on all-cause mortality (RR, 1.18; 95% CI, 1.09 to 1.28; P < 0.0001) and heart failure rehospitalization (RR, 1.42; 95% CI, 1.18 to 1.71; P = 0.0002). There was no difference in long-term cardiovascular mortality between the two groups (RR, 1.15; 95% CI, 0.97 to 1.36; P = 0.11). Left ventricular ejection fraction (LVEF) was not significantly different at baseline (mean difference, 1.40; 95% CI, -0.13 to 2.93; P = 0.07), but was significantly lower in the PPI group at 1-year follow-up (mean difference, -3.57; 95% CI, -4.88 to -2.26; P < 0.00001). Conclusion: Our meta‐analysis provides evidence that post-TAVR PPI has negative clinical and echocardiographic effects on patients at mid- to long-term follow-up. Further studies are urgently needed to explore the cause of these complications and optimize the treatment and management of patients requiring permanent pacing after TAVR.